Investigation of the Effect of CFRP and GFRP Sheet Length on the Final Capacity of Reinforced Concrete Beams of Buildings in Coastal Areas - Mashhadi, Ali Rasoulian; Varastehpour, Hamid; Ghassemizadeh, Seyed Mahmood (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2024)
In the last two decades, the use of FRP (Fiber Reinforced Polymer) composites for flexural, shear, torsion, and enclosing reinforcement of various structural components has grown exponentially. In this paper, the effect of using FRP composite with carbon fibers and glass with different lengths on the behavior of reinforced concrete beams is investigated. Eight reinforced concrete beams with a length of 150 cm, a width of 15 cm, and a height of 20 centimeters were modeled by composite fibers with lengths of 80 cm, 100 cm, 120 cm and 140 centimeters. Then, the sample reinforced concrete beam was modeled in ABAQUS® , which the results were compared with the laboratory samples. It were observed that with increasing the length of FRP sheets, the strength of reinforced concrete beams compared to the sample concrete beam, increased by about 61%, 82%, 86%, and 87%, respectively. It was due to the high cost of FRP sheets and compressive strength required in these sheets that used optimally. Therefore, the length of FRP strengthening sheets can be optimized to reduce the cost of FRP sheets and use them efficiently.